Isolated Kaposi Sarcoma of the Tonsil: A Case Report and Review of the Scientific Literature. (10th February 2015) - Pittore, Barbara; Pelagatti, Carlo Loris; Deiana, Francesco; Ortu, Francesco; Maricosu, Elena; Cossu, Sergio; Sotgiu, Giovanni
Abstract : Kaposi sarcoma is a tumour caused by human herpes virus 8, also known as Kaposi sarcoma-associated herpes virus. It usually affects the skin and oral mucosa; however, it can also sometimes affect the lungs, the liver, the stomach, the bowel, and lymph nodes. Several body sites may be affected simultaneously. The involvement of the tonsils is rare. We described an isolated localization of Kaposi's sarcoma of the right tonsil in a HIV-positive patient.